A three-start helical sheath on the flagellar filament of Caulobacter crescentus. - Trachtenberg, S (1992)
An unusual feature in preparations of the Caulobacter crescentus flagellar filaments is that some filaments are surrounded by a set of three windings that form a sheath. We provide evidence that the sheath is composed of subunits having a molecular mass of 24,000 Da. We suggest that the sheath could be composed of protofilaments of flagellin wound around the filament.